Teachers' readiness and challenges in implementing differentiated instruction in mathematics education - Fitri Novriyeni; Yenita Roza; Sehatta Saragih (State Islamic University of North Sumatra, 2025)
Differentiated instruction, a key component of the contemporary learning paradigm, aims to tailor teaching strategies to students' varied needs. Despite its pedagogical relevance, this approach has yet to become a central focus among classroom practices. This study examines the readiness of junior high school mathematics teachers in Pekanbaru City to implement differentiated instruction. Employing a descriptive quantitative design, data were collected from 30 participants via an online questionnaire. The instrument included closed-ended items measured on a Likert scale across four dimensions: (1) conceptual understanding of differentiated instruction, (2) readiness in instructional planning, (3) readiness in classroom implementation, and (4) readiness in assessment practices. Open-ended items were also included to explore implementation challenges. The results reveal a low overall level of understanding and readiness, with an average score of 2.49 across all measured dimensions. Key barriers include limited access to information, insufficient time allocation, and unsupportive learning environments. This study provides empirical insights into instructional preparedness and practical constraints, offering a basis for future interventions aimed at strengthening the adoption of differentiated instruction in mathematics education.